2018
DOI: 10.12688/f1000research.16820.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postoperative pain in infected root canals after using double antibiotic paste versus calcium hydroxide as intra-canal medication: A randomized controlled trial

Abstract: Background: Postoperative pain is defined as pain of any degree after initiation of endodontic treatment either intra-appointment or post-obturation and is considered an undesirable occurrence for both patient and dentist. It was suggested that bacterial injury is probably the major cause of pain. Intra-canal medicaments are widely used to kill any bacteria surviving after instrumentation and irrigation. The aim of this study was to assess the ability of double antibiotic paste versus calcium hydroxide used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 26 publications
0
15
2
Order By: Relevance
“…Contrary to our results one study noticed no advantage of DAP medication over CH, but they used canal dressings for 48 hours only 16 . With contrast to our findings Narang K 2018 20 found no difference between antibiotic pastes and CH in apical periodontitis in their case reports.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our results one study noticed no advantage of DAP medication over CH, but they used canal dressings for 48 hours only 16 . With contrast to our findings Narang K 2018 20 found no difference between antibiotic pastes and CH in apical periodontitis in their case reports.…”
Section: Discussioncontrasting
confidence: 99%
“…Sabbagh S 2018 11 also found symptom free patient when they applied DAP as intracanal medication in their case report. Contrary to our results Abouelenien SS 2018 16 in their study found less post operative pain in apical periodontitis with DAP group than CH after only 24 hours, while we evaluated postoperative pain after 7 days.…”
Section: Discussioncontrasting
confidence: 94%
“…Twenty-six articles were excluded for different reasons ( Supplementary Table 4 ). Sixteen articles from 15 studies [ 4 5 10 11 12 20 21 22 23 24 25 26 27 28 29 30 ] were included in the qualitative analysis ( Tables 1 and 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen articles [ 4 5 10 11 12 20 21 24 25 26 27 29 30 ] assessed postoperative pain in terms of incidence and/or intensity using different scales. Five articles reported flare-up incidence [ 20 22 23 25 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation